2021
DOI: 10.1186/s12905-021-01452-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of endometrial cancer in patients with endometrial hyperplasia: implication for clinical treatments

Abstract: Background Endometrial hyperplasia (EH) is commonly-seen in the patients with endometrial cancer (EC), we aimed to evaluated the risk factors of EC in patients with EH, to provide evidence to the clinical prevention and treatment of EC. Methods This study was a retrospective study design. EH patients confirmed by pathological examinations and treated with hysterectomy in our hospital from June 1, 2018 to February 28, 2021 were included. The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
2
0
2
Order By: Relevance
“…These ndings are consistent with a meta-analysis conducted by Aune et al [46], where an OR of 1.61 was obtained (however, when considering only case-control studies, the OR was 1.73). Moreover, the study conducted by Zhao and colleagues showed an OR of 2.7 (although the study group was relatively small) [71]. The role of hypertension in the development of endometrial cancer was also demonstrated in the studies by Yang and colleagues [72], as well as Giordano and colleagues [73].…”
Section: Discussionmentioning
confidence: 83%
“…These ndings are consistent with a meta-analysis conducted by Aune et al [46], where an OR of 1.61 was obtained (however, when considering only case-control studies, the OR was 1.73). Moreover, the study conducted by Zhao and colleagues showed an OR of 2.7 (although the study group was relatively small) [71]. The role of hypertension in the development of endometrial cancer was also demonstrated in the studies by Yang and colleagues [72], as well as Giordano and colleagues [73].…”
Section: Discussionmentioning
confidence: 83%
“…Zhao et al, evaluated the risk factors for endometrial cancer in patients with endometrial hyperplasia. They found that the incidence of endometrial cancer was 31.58% in a total of 228 patients with endometrial hyperplasia, of whom 72 had endometrial cancer 20 . In this study, the first two SM indications were myoma uteri and AUB, and the fifth SM indication was endometrial hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Lachance et al (2006), the average BMI of patients <45 yo was 40.3 kg/m 2 compared to older patients (35.3 kg/m 2 in 46-64 yo and 31.0 kg/m 2 in those >65 yo) [7]. In a meta-analysis of BMI, the risk of EC increased more obviously when BMI was 25 or greater [23,30]. In one study by Pellerin & Finan (2005), 71% of patients <45 yo with EC had a BMI of 30 or greater [31].…”
Section: Obesitymentioning
confidence: 99%